Malmquist Theorem for the Solutions of Differential Equations in the Vicinity of a Branching Point - Mokhonko, A. Z.; Mokhonko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
An analog of the Malmquist theorem on the growth of solutions of the differential equation f’ = P(z, f)/Q(z, f), where P(z, f) and Q(z, f) are polynomials in all variables, is proved for the case where the coefficients and solutions of this equation have a branching point in infinity (e.g., a logarithmic singularity).